SPE Annual Technical Conference and Exhibition 2002
DOI: 10.2118/77425-ms
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of a Deepwater Turbidite Reservoir Conditional to Seismic Data Using Multiple-Point Geostatistics

Abstract: Geological interpretation and seismic data analysis provide two complementary sources of information to model reservoir architecture. Seismic data affords the opportunity to identify geologic patterns and features at a resolution on the order of 10's of feet, while well logs and conceptual geologic models provide information at a resolution on the order of one foot. Both the large-scale distribution of geologic features and their internal fine-scale architecture influence reservoir performance. Development and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…Indeed, these methods are able to describe smoothly heterogeneous media but inadequate when facing complex structures (Strebelle et al, 2002) such as multimodal distributions, with interconnected and curvilinear structures, those of alluvial plains or turbiditic reservoirs for example. To overcome these limitations, multiple-point statistics can be used.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, these methods are able to describe smoothly heterogeneous media but inadequate when facing complex structures (Strebelle et al, 2002) such as multimodal distributions, with interconnected and curvilinear structures, those of alluvial plains or turbiditic reservoirs for example. To overcome these limitations, multiple-point statistics can be used.…”
Section: Discussionmentioning
confidence: 99%
“…By scanning this training image and storing the corresponding training multiple-point statistics, mpgeostatistics achieves a reasonable level of shape reproduction. Reservoir case studies have demonstrated this successfully 3,4 . However, due to the pixel-based nature of mp geostatistics, objects with sharp corners and extremely curvilinear objects like oxbows would be poorly reproduced.…”
Section: Introductionmentioning
confidence: 93%
“…6). Strebelle et al 4 present a method for extracting geobody information from seismic amplitude data on the same data set. Strebelle et al extracted two types of information from the post-stack amplitude: (1) a 3D cube of geobodies obtained from applying a clustering method on realizations of windowed seismic amplitudes, Fig.…”
Section: Application To Submarine Channel Reservoirmentioning
confidence: 99%
See 1 more Smart Citation
“…The field of geostatistical modeling focuses on creating models depicting subsurface hydrogeology and/or reservoir properties. Geostatistics is currently applied in a number of geoscience fields, such as petrology (e.g., Okabe and Blunt, 2005), petroleum reservoir modeling (e.g., Journel and Zhang, 2006;Strebelle et al, 2002), hydrogeology (e.g., Huysmans and Dassargues, 2009) and hydrology (e.g., Michaelides and Chappell, 2009). Overall geostatistical methods provide a framework in which multiple equiprobable hydrostratigraphic models can be created in a semiautomated fashion.…”
mentioning
confidence: 99%